2020
DOI: 10.31436/ijcs.v3i2.164
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Cognitive Impairment Among Older People Living In Old Folk Homes, Malaysia

Abstract: Introduction: Cognitive impairment is common among older people living in old folk homes due to several factors including the aging process and moving to unfamiliar places. The present study aimed to explore the prevalence rates and factors associated with cognitive impairment in older people living in old folk homes RACF. Methods: A cross-sectional study was conducted on 167 older people aged 60 years and over living in two old folk homes in Malaysia. A questionnaire consists of three parts; sociodemographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
0
1
Order By: Relevance
“…Living with a spouse was found to be a protective factor against CI in our study, which agreed with the findings of other studies [ 15 , 18 , 20 , 23 , 25 , 26 , 31 ]. Being alone in old age can be difficult, considering the occurrence of degenerative physical and psychological changes.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Living with a spouse was found to be a protective factor against CI in our study, which agreed with the findings of other studies [ 15 , 18 , 20 , 23 , 25 , 26 , 31 ]. Being alone in old age can be difficult, considering the occurrence of degenerative physical and psychological changes.…”
Section: Discussionsupporting
confidence: 94%
“…We found that CI (in any form) had a prevalence of 91.7%, with 28.6% of participants exhibiting severe CI. Our study found a higher prevalence of CI compared to studies conducted elsewhere, which reported a prevalence ranging from 4.5% to 71.9% [ 15 - 23 ]. The higher prevalence in our study can be ascribed to the study group’s profile, with all participants ≥65 years of age, ranging from 65 to 95 years.…”
Section: Discussioncontrasting
confidence: 67%